1975
DOI: 10.1136/jcp.28.6.428
|View full text |Cite
|
Sign up to set email alerts
|

A perinatal mortality survey in south-east London, 1970-73: the pathological findings in 726 necropsies.

Abstract: The primary necropsy finding are presented for 726 perinatal deaths; the classification of the 1958 British Perinatal Mortality Survey is used, and results of the two surveys are compared. Lethan malformation has replaced intrapartum hypoxia as the most common cause of perinatal death. There has been substantial reduction in intracranial trauma but an increase in intraventricular haemorrhage and, possible, extrapulmonary infection. Chromosome abnormalities occurred in 28 of 500 karyotyped infants (5-6 per cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
2

Year Published

1976
1976
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 15 publications
2
6
2
Order By: Relevance
“…e incidence of stillbirth reported from western countries ranges from 4.7% to 12.0%. [4][5][6][7][8][9][10] is is lower than that observed in our study. e reason could be a high number of unsupervised deliveries due to various reason like literacy, low socioeconomic status and the paucity of monitoring facilities in rural areas.…”
Section: Discussioncontrasting
confidence: 56%
“…e incidence of stillbirth reported from western countries ranges from 4.7% to 12.0%. [4][5][6][7][8][9][10] is is lower than that observed in our study. e reason could be a high number of unsupervised deliveries due to various reason like literacy, low socioeconomic status and the paucity of monitoring facilities in rural areas.…”
Section: Discussioncontrasting
confidence: 56%
“…Studies on our hospital population confirm recent findings (Machin, 1975) of an absolute increase in the incidence of IVH as compared to the 1958 Perinatal Mortality Survey. Part of our high incidence results from the large number of low birthweight infants in our population, but there is a trebled incidence in deaths from IVH in the 1000-1500 g birthweight group.…”
Section: Discussionsupporting
confidence: 89%
“…Since it has been suggested that the increasing incidence of IVH in infants dying with HMD may be due to the survival of a larger number of such babies until the age when IVH supervenes (Machin, 1975), we compared the survival times of our infants with those reported from the British Perinatal Mortality Survey ( (Table III). There was a tendency for the babies who died with IVH to be smaller and less mature than those who had HMD alone, but the difference was not significant.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of excluding twins who did not survive is related to the sex ratio of birth defects among stillbirths and abortions. In the general population, this sex ratio (males to females) is close to unity in spontaneously aborted human embryos (Byrne and Warburton, 1987) and stillbirths (McKeown and Lowe, 1951;Naeye et al, 1971;Machin, 1975). However, very little information is available about the sex ratio in birth defects among aborted or stillborn opposite-sex twins.…”
Section: Discussionmentioning
confidence: 93%